Shear strength of steel-reinforced ultra-high performance concrete dry and epoxy joints for segmental girders - Gopal, Balamurugan A. (2019)
Joints in precast segmental bridge girders (PSBGs) are the locations of discontinuity and these parts are weaker than those of adjacent monolithic sections within the segment. During the service phase, the compression and shear forces are transmitted at this component. Generally, the keys in this region serve three purposes, namely, to align the segments during erection, to transfer shear force between the sections during service, and to protect the prestressing tendons against corrosion where the tendons pass through the joints. However, as revealed in this study, all the existing provisions tended to significantly over-estimate the ultimate shear capacity of the joint specimens and are developed for normal grade concretes which cannot be used in ultra-high performance fibre reinforced concrete (UHPFRC) joints of PSBGs. The literature review also highlighted that there was no available existing design provision model to calculate the first crack shear capacity of any type of concrete keyed joints.